2020
DOI: 10.1093/mnras/staa3183
|View full text |Cite
|
Sign up to set email alerts
|

Network of thermal cracks in meteorites due to temperature variations: new experimental evidence and implications for asteroid surfaces

Abstract: In recent years several studies have shown the importance of thermal fracturing of rocks due to temperature variations, on Earth and Mars. Rock thermal cracking might also be a process at play on the lunar surface. These temperature variations as well as change rates can reach important amplitude on bodies without an atmosphere, in particular on those that reach small perihelion distances such as near-Earth asteroids. On the other hand, the formation, geometry and extension of cracks on these bodies have not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 62 publications
2
36
0
Order By: Relevance
“…Many returned particles feature curved and straight cracks. Pebbles with a smooth surface could be fragments of particles with straight cracks, possibly formed by shock or thermal fatigue ( 33 ). The common presence of cracks in returned pebbles implies that the small thermal inertia of surface boulders ( 12 , 13 ) is probably due, at least in part, to cracks or fractures in their interior.…”
Section: Samples Returned To Earthmentioning
confidence: 99%
“…Many returned particles feature curved and straight cracks. Pebbles with a smooth surface could be fragments of particles with straight cracks, possibly formed by shock or thermal fatigue ( 33 ). The common presence of cracks in returned pebbles implies that the small thermal inertia of surface boulders ( 12 , 13 ) is probably due, at least in part, to cracks or fractures in their interior.…”
Section: Samples Returned To Earthmentioning
confidence: 99%
“…Internal stresses caused by differential thermal expansion, as a result of cyclic heating and cooling, lead to regolith breakdown and erosion (Eppes et al 2015). The efficiency of this thermal cycling process has been modeled under the thermal environments of airless solar system bodies (e.g., Molaro & Byrne 2012;Molaro et al 2017), and its feasibility has been experimentally demonstrated on meteorite samples (Delbo et al 2014;Libourel et al 2020). Molaro et al (2020) demonstrated that large cracks observed on rocks seen across Bennu's surface were consistent with thermal fatigue model predictions.…”
Section: Introductionmentioning
confidence: 72%
“…It has been debated whether or not thermal fracturing is a relatively significant weathering mechanism for terrestrial rocks (e.g., Molaro & McKay 2010, and references within), yet Delbo et al (2014) experimentally demonstrated the effectiveness of this process, in vacuo, on a chip of the Murchison (CM2 carbonaceous chondrite) and Sahara 97210 (L/LL3.2 ordinary chondrite) meteorites. Libourel et al (2021) performed a followup study with these two meteorites and Allende (CV3), where they demonstrated that larger temperature gradients, such as those experienced for low perihelion asteroids, result in greater crack growth rates. Images from the encounter of Bennu by OSIRIS-REx provided widespread evidence of thermal cracking across the surface (Molaro et al 2020).…”
Section: Thermal Fatigue Breakdownmentioning
confidence: 99%
“…The efficiency of thermal fatigue should even increase for bodies with low perihelion distances, i.e., experiencing intense temperature variations, and bodies composed of hydrated minerals, which may experience dehydration. Experiments were performed on meteorites using very high temperature variations to demonstrate the increased efficiency of thermal fatigue for low perihelion objects [154]. In these experiments, meteorites composed of hydrated minerals experienced dehydration, enhancing the cracking process.…”
Section: Thermal Effects On Asteroidsmentioning
confidence: 99%